The mediating role of anticipated consumer emotions on the relationship between human-induced scarcity and value perception among selected generation Y and Z Filipino consumers of Shopee - Afurong, Beatrice Marie Dacanay (Animo Repository, 2022)
An organization’s success heavily relies on the strategies being implemented. Past literature has shown that some of the most effective strategies revolve around the concepts of scarcity appeals or value perception in brick and mortar stores. In the current business landscape, several companies shifted online, evidently causing consumers to become more dependent on e-commerce platforms. As such, this study examines the mediating role of anticipated consumer emotions on the relationship between human-induced scarcity and value perception among selected generation Y and Z Filipino consumers of Shopee (N=200). Results revealed that anticipated consumer emotions partially mediated (p < 0.001) the relationship between scarcity and value, hence, implying that scarcity still directly influences value (p < 0.001) even when the mediator is omitted. On a more specific note, however, the researchers obtained a better model fit (Adjusted R2 = 0.200) when incorporating a mediator between the response and predicting variables. With this, it is recommended for online entrepreneurs and Shopee to impose scarcity appeal strategies, specifically time-induced and quantity-induced scarcity. This was because it was revealed that doing so stimulates two main primary drivers of purchase intention - consumer emotions, and value perception. Thus, enabling them to further strengthen their competitive advantage.